In cammino verso l’Altro: Essenza e sofferenza del linguaggio tra Heidegger e Levinas - Bottacin Cantoni, Nicoletta (Scenari, 2021)
The essay analyses the speculation concerning the origin and the essence of language in Levinas and in his criticism of Heideggerian philosophy. Levinas argues that Heidegger lacks of a proper meditation on the notion of body, thus Heideggerian philosophy does not involve a true ethical dimension. First of all, Levinas tries to overcome ontology, since Heideggerian thought is based on the notion of Being and on the relation between man and being. This relation is inadequate to explain the inter-human bond. Then Levinas reconsiders the temporality based on the notion of embodiment: only if time arises from the relationship with the Other and the other human beings, it is possible to find the origin of language. Language comes from the ab-original, traumatic experience of the face of the other and from the generous response I am obliged to give. Moreover, Levinasian translation of Heideggerian categories highlights how deeply Levinas understood and assimilated the master’s lesson, but it also proves that the Author provided an original alternative to Heideggerian philosophy of essence by subordinating being to the generosity for the other.